Estudo do potencial de utilização do resíduo da extração de esmeraldas na fabricação de cerâmica de revestimento - Cavalcante, Ronaldo Fonseca (2010)
Companies involved in emerald mining and treatment represent an important area of industrial development in Brazil, with significative contribution to the worldwide production of such mineral. As a result, large volumes of emerald waste are constantly generated and abandoned in the environment, negatively contributing to its preservation. By the other side the interest of the use of mining waste as additive in ceramic products has been growing from researchers in recent years. The ceramic industry is constantly seeking to the marked amplification for the sector and perfecting the quality of the products and to increase the variety of applications. The technology of obtaining of ceramic tiles that uses mining residues assists market niches little explored. In this scenario, the objective of the present study was to characterize the residue generated from emerald mining as well as to assess its potential use as raw material for the production of ceramic tiles. Ceramic mixtures were prepared from raw materials characterized by X-ray fluorescence, X-ray diffraction, particle size analysis and thermal analysis. Five compositions were prepared using emerald residue contents of 0%, 10%, 20%, 30% and 40%. Samples were uniaxially pressed, fired at 1000, 1100 and 1200ºC and characterized aiming at establishing their mineralogical composition, water absorption, apparent porosity, specific mass, linear retraction and modulus of rupture. The results shows that the emerald residue, basically consisted of 73% of (SiO2 + Al2O3) and 17,77% of (MgO + Na2O+ K2O) (that facilitates sintering), can be added to the ceramic tile materials with no detrimental effect on the properties of the sintered products